Police response to domestic violence: Theoretical framework and foreign experiences - Konstantinović-Vilić Slobodanka D.; Petrušić Nevena (Temida)
This paper is dedicated to recognizing police work and intervention in the cases of domestic violence. Keeping in mind the relationship between the offender and the victim in the cases of domestic violence, seriousness of the consequences, as well as the fact that, during the intervention, police is the first state agency which “disturbs” the sphere of family privacy, it is very important to study the way police is reacting, establish the degree of its efficiency and explore the factors that determine the efficiency of police intervention. The paper points out the policy of police response to domestic violence in some foreign systems (Great Britain, USA, Australia). Particular attention is paid to consideration of activities police is dealing with while collecting the data on the violence, victim and the offender, the way police is reacting in order to prevent new violence, as well as the responsibility and aims police has during the intervention.